The effect of interstitial carbon atoms on defect evolution in high entropy alloys under helium irradiation. (July 2022) - Su, Zhengxiong; Shi, Tan; Yang, Jinxue; Shen, Huahai; Li, Zhiming; Wang, Sheng; Ran, Guang; Lu, Chenyang
Graphical abstract: Image, graphical abstract Abstract: In this work, a design strategy based on a typical multi-principal element alloy (Fe50 Mn30 Co10 Cr10, at. %) was proposed to tune the irradiation behavior by adding interstitial carbon atoms (Fe49.5 Mn30 Co10 Cr10 C0.5, at. %). Advanced scanning transmission electron microscopy was employed to study the evolution of dislocation loops and helium bubbles in alloys after 400 keV He + ion irradiation at three different temperatures ranging from 350 °C to 450 °C. The results showed that the interstitial carbon atoms inhibited the growth of He bubbles and irradiation hardening. The high-resolution energy dispersive spectroscopy mapping revealed that the segregation at the dislocation loops in Fe49.5 Mn30 Co10 Cr10 C0.5 was efficiently lessened compared to that in Fe50 Mn30 Co10 Cr10, which shows an even superior performance than the equiatomic FeMnCoCrNi Cantor alloy. Radiation-induced "W-shaped" elemental oscillation patterns with a width of about 1 nm around dislocation loops, were observed for the first time in high-entropy alloys. Such nanoscale local elemental fluctuations are suggested to modify the lattice friction and thus have an impact on the mechanical properties of the material. First-principles calculations suggest that the interstitial carbon atoms can effectively enhance the site-to-site local lattice distortion and modify vacancy migration energy near carbon atoms. Our systematic experiments demonstrate that adding interstitial carbon atoms into multi-principal element or high-entropy alloy is beneficial for the reduction in irradiation hardening and volumetric swelling, as well as radiation-induced segregation.